Fireproof plate and preparation method thereof
By using wood powder, silicate compounds and phenolic resin substrates and glass fiber mesh reinforcement layers, combined with fire-resistant coatings such as hollow glass microbeads, the problem of structural damage of fire-resistant plates in high temperature environments is solved, and efficient fire-proof and thermal insulation performance is achieved.
Patent Information
- Application Number
- CN202411723876.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
Existing fire-proof boards deform due to uneven thermal stress in high temperature environments, resulting in structural damage and degradation of fire-proof performance.
Wood powder, silicate compounds and phenolic resin binder are used as the substrate, and glass fiber mesh is coated on both sides of the substrate as a reinforcement layer, and a fire-retardant coating containing hollow glass microbeads, ammonium polyphosphate, nanometal oxide and other components are coated on the surface.
It significantly improves the high temperature resistance and fire resistance of the plate, effectively resists thermal stress deformation and fire spread, and ensures the structural integrity of the plate under high temperature environment.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and more specifically, to a fireproof board and a preparation method thereof. Background Art
[0002] Fireproof panels, as an important building material, are widely used in various fields of the construction industry, especially in places with extremely high fire safety requirements. With its excellent fireproof performance, good physical and mechanical properties and environmental protection characteristics, it has become an indispensable part of modern architectural design. Fireproof panels can not only effectively prevent the spread of fire and reduce fire losses, but also maintain structural integrity in fires, buying precious time for personnel evacuation and rescue.
[0003] At present, the common fireproof boards on the market mostly use inorganic mineral materials as the main components, and are made through specific process formulas and molding technologies. These materials include but are not limited to silicates, magnesium hydroxide, aluminum oxide, etc., which have the characteristics of high thermal stability, non-flammability and low smoke generation. During the manufacturing process, these inorganic mineral materials are usually mixed with organic or inorganic binders, reinforcing fibers (such as glass fibers, basalt fibers) and appropriate amounts of fillers and additives, and are made into boards through processes such as mixing, molding, and curing.
[0004] Regarding the above-mentioned related technologies, although they have made some progress in improving the fire resistance time of fireproof panels, they are still obviously insufficient in improving the fireproof effect (especially the thermal insulation performance and resistance to high temperature deformation). Specifically, in a high temperature environment, the internal materials of existing fireproof panels often deform due to uneven thermal stress, resulting in the destruction of the overall structure of the panel and a significant reduction in fireproof performance. Summary of the invention
[0005] In order to improve the fireproof and flame retardant effects of a fireproof board, the present application provides a fireproof board and a preparation method thereof.
[0006] In the first aspect, the present application provides a fireproof board, which adopts the following technical solution: A fireproof board, comprising a substrate, a reinforcing layer coated on both sides of the substrate, and a fireproof coating coated on the outer surfaces of both sides of the board, wherein the substrate comprises wood powder, a silicate compound and a phenolic resin adhesive, both sides of the substrate are coated with glass fiber mesh as a reinforcing layer, and the surface is coated with the fireproof coating; The fire retardant coating comprises the following raw materials in parts by weight: 20-30 parts of hollow glass microspheres, 10-15 parts of ammonium polyphosphate, 5-10 parts of nano metal oxides, 10-15 parts of magnesite, 5-10 parts of tetraethyl orthosilicate, 15-30 parts of epoxy resin, and 30-40 parts of water.
[0007] By adopting the above technical solution, using wood powder, silicate compounds and phenolic resin adhesive as the base material, not only the basic strength and stability of the board are enhanced, but also its high temperature resistance is significantly improved. The glass fiber mesh cloth is coated on both sides of the base material as a reinforcement layer to further strengthen the board structure and effectively resist external impact and thermal stress deformation. What is particularly critical is that the surface is coated with fire retardant coating. Its unique formula combines the thermal insulation effect of modified hollow glass microspheres, the fire resistance of magnesia, the flame retardant properties of ammonium polyphosphate and the catalytic effect of nano-metal oxides, supplemented by the excellent film-forming and weather resistance of tetraethyl orthosilicate and epoxy resin, forming an indestructible fire barrier, which not only greatly improves the fire resistance level of the board, effectively delays the spread of fire, but also maintains the structural integrity of the board in high temperature environments.
[0008] Optionally, the fire retardant coating further comprises 3-8 parts of modified molecular sieves, into which phosphorus and fluorine elements are introduced.
[0009] By adopting the above technical solution, under long-term burning in a high-temperature environment, some components in the coating may produce free radicals, which in turn trigger a chain reaction and cause the coating to burn. The molecular sieve can adsorb these free radicals and interrupt the chain reaction, thereby reducing the combustion risk of the coating and further improving the fire retardant effect of the coating. At the same time, the molecular sieve added can synergize with the ammonium polyphosphate in the coating to reduce the generation of amorphous carbon during combustion, stabilize the carbon layer structure, effectively prevent the carbon layer from bursting, delay the combustion of the inner layer substrate, and greatly reduce the peak value of the second exothermic peak and delay the peak time, reducing the danger of the board in a fire. Further loading flame-retardant metal elements further improves the fire retardant effect of the board.
[0010] Optionally, the preparation of the modified molecular sieve comprises the following steps: Weigh a molecular sieve and soak it in a mixed solution of hypophosphite and 1-butyl-3-methylimidazolium tetrafluoroborate, stir it at room temperature for 1-2 hours, grind it into powder, and dry it to obtain a product.
[0011] By adopting the above technical solution, due to the porous structure of the molecular sieve, the metal active ingredients can be very evenly dispersed in the carrier, which is conducive to molecular movement and reduces the smoke generated by combustion. At the same time, its thermal insulation function can effectively inhibit convective heat transfer, reduce solid-state heat conduction, and improve the flame retardant effect of the material.
[0012] As a room temperature ionic liquid, BMIMBF4 has extremely low vapor pressure, high thermal stability and good solubility. These characteristics enable it to form a stable and high temperature resistant solution system after mixing with hypophosphite. During the soaking process of the molecular sieve, the mixed solution can penetrate into the pore structure of the molecular sieve, which not only enhances the mechanical strength of the molecular sieve, but also improves the heat resistance of the overall material through its unique chemical structure. Among them, hypophosphite serves as a phosphorus source, and the fluoroborate in BMIMBF4 provides a fluorine source. Through soaking and stirring, these elements have the opportunity to react with hydroxyl groups or other active sites on the surface of the molecular sieve, and are successfully introduced into the skeleton or pores of the molecular sieve. Hypophosphite can decompose at high temperatures to produce phosphoric acid and other phosphorus-containing compounds. These compounds can form a dense protective layer at high temperatures, effectively isolating oxygen and heat, thereby preventing or slowing down further combustion of the material. The addition of BMIMBF4 further enhances the formation ability and stability of this protective layer, so that the material can still maintain good structural integrity and fire resistance in extremely high temperature environments.
[0013] Optionally, the weight ratio of the molecular sieve to the hypophosphite and 1-butyl-3-methylimidazolium tetrafluoroborate is 1:0.3:0.5-1.
[0014] Optionally, the glass fiber mesh is pretreated, and the pretreatment comprises the following steps: The glass fiber mesh cloth is immersed in a dipping solution mixed with silicone acrylate and polyester solution for 2-3 hours, irradiated with ultraviolet light for 3-5 minutes, and dried to obtain the pretreated fiber cloth.
[0015] By adopting the above technical scheme, the dipped glass fiber mesh produces cross-linking and curing reactions under ultraviolet light, so that the silicone acrylate and polyester are more firmly attached to the glass fiber mesh, thereby realizing the modified pretreatment of the glass fiber mesh. The pretreated glass fiber mesh can maintain stability in a high temperature environment and provide long-lasting protection for the plate. At the same time, the polyester material loaded thereon can undergo a ring-opening reaction with the skeleton material epoxy resin in the coating, thereby further improving the bonding strength between the fire retardant coating and the substrate.
[0016] Optionally, the weight ratio of silicone acrylate and polyester added to the dipping solution is 2-4:1-1.5.
[0017] The polyester is a water-soluble polyester.
[0018] In a second aspect, the present application provides a method for preparing a fireproof board, which adopts the following technical solution: A method for preparing a fireproof board comprises the following steps: The wood powder and silicate compound are mixed and stirred evenly, and the phenolic resin solution is evenly sprayed and added. After high-speed stirring and mixing, a layer of glass fiber mesh is laid on the upper and lower surfaces of the matrix respectively, and a preliminary board matrix is formed through a hot pressing process; The inorganic fireproof coating is coated on the surface of the preliminary board substrate and cured to obtain the fireproof board.
[0019] Optionally, the substrate comprises 80-100 parts of wood flour, 10-20 parts of silicate compounds and 8-15 parts of phenolic resin in parts by weight.
[0020] By adopting the above technical solution, the preparation method is easy to operate and is conducive to industrial production. The application of hot pressing process makes the plate forming more uniform and dense, improving production efficiency and product quality. At the same time, the application of inorganic fire retardant coating and maintenance steps are also relatively simple and easy to control.
[0021] In summary, this application has the following beneficial effects: 1. Since the present application uses wood powder, silicate compounds and phenolic resin adhesive as the base material, it not only enhances the basic strength and stability of the board, but also significantly improves its high temperature resistance. The fire retardant coating coated on its surface combines a variety of high-efficiency fire retardant ingredients, such as hollow glass microspheres, ammonium polyphosphate, nano-metal oxides, etc., to form a powerful fire barrier, greatly improve the fireproof level of the board, effectively delay the spread of fire, and ensure the structural integrity of the board in a high temperature environment. At the same time, the introduction of modified molecular sieves can adsorb free radicals and interrupt chain reactions, further improving the fireproof effect of the coating and reducing the danger of the board in a fire.
[0022] 2. The glass fiber mesh wrapped on both sides of the substrate in this application serves as a reinforcement layer, which not only strengthens the board structure and effectively resists external impact and thermal stress deformation, but also further improves its stability in high temperature environments through pretreatment processes. The silicone acrylate and polyester attached to its surface help the board remain stable at high temperatures and can react with the epoxy resin in the coating to further enhance the bonding strength between the fire retardant coating and the substrate, thereby improving the overall durability of the board.
[0023] 3. The method of the present application uses wood powder, a renewable resource, as one of the main raw materials, which reduces the dependence on traditional wood resources and reduces environmental pressure. At the same time, the formula design fully considers environmental factors, and the raw materials used are mostly non-toxic or low-toxic materials, which is conducive to reducing environmental pollution during production and use. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments.
[0025] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0026] The wood powder is poplar wood powder, with a density of 3.65kg / m 2 , purchased from Feixian Weichao Wood Processing Factory; 1-butyl-3-methylimidazole tetrafluoroborate was purchased from Jining Tangyi Chemical Co., Ltd., item number: PZ51313523; molecular sieve was purchased from Ruizhian New Materials (Shandong) Co., Ltd., model 13X, SiO2 / Al2O3 is 2.4%; epoxy resin model E44; phenolic resin was purchased from Jinan Dahui Chemical Technology Co., Ltd., model 2123; polyester resin is a water-based polyester purchased from Jining Tangyi Chemical Co., Ltd., item number WBO-144.
[0027] Preparation example of modified molecular sieve Preparation Example 1 A modified molecular sieve, the preparation of which comprises the following steps: 10 kg of molecular sieve was weighed and immersed in a mixed solution of 3 kg of aluminum hypophosphite and 7.5 kg of 1-butyl-3-methylimidazolium tetrafluoroborate, stirred at room temperature for 2 hours, crushed and ground using a dispersing and stirring multi-purpose machine, and dried at 105° C. to obtain the modified molecular sieve.
[0028] Preparation Example 2 A modified molecular sieve, the preparation of which comprises the following steps: 10 kg of molecular sieve was weighed and immersed in a mixed solution of 3 kg of hypophosphite and 10 kg of 1-butyl-3-methylimidazolium tetrafluoroborate, stirred at room temperature for 1.5 hours, crushed and ground using a dispersing and stirring multi-purpose machine, and dried at 105° C. to obtain the modified molecular sieve.
[0029] Preparation Example 3 A modified molecular sieve, the preparation of which comprises the following steps: 10 kg of molecular sieve was weighed and immersed in a mixed solution of 3 kg of hypophosphite and 5 kg of 1-butyl-3-methylimidazolium tetrafluoroborate, stirred at room temperature for 1 hour, crushed and ground using a dispersing and stirring multi-purpose machine, and dried at 105° C. to obtain the modified molecular sieve.
[0030] Preparation example of fire retardant coating Preparation Example 4 A fire retardant coating, the preparation of which comprises the following steps: Hollow glass microspheres, modified molecular sieves, and nano-alumina are added to tetraethyl orthosilicate and dispersed evenly in water to obtain a mixed solution; ammonium polyphosphate, magnesia, and epoxy resin are added to the mixed solution and mixed evenly to obtain the interior wall insulation coating, and the modified molecular sieve is prepared in Preparation Example 1.
[0031] Preparation Example 5-6 A fire retardant coating, which is different from Preparation Example 1 in that the raw material components and their corresponding weight portions are shown in Table 1.
[0032] Preparation Example 7 A fire retardant coating, which is different from Preparation Example 1 in that the modified molecular sieve used in this Preparation Example is prepared by Preparation Example 2.
[0033] Preparation Example 8 A fire retardant coating, which is different from Preparation Example 1 in that the modified molecular sieve used in this Preparation Example is prepared by Preparation Example 3.
[0034] Preparation Example 9 A fire retardant coating, which is different from Preparation Example 1 in that no molecular sieve is added in this Preparation Example.
[0035] Preparation Example 10 A fire retardant coating, which is different from Preparation Example 1 in that the molecular sieve added in this Preparation Example is not modified.
[0036] Table 1 Raw materials and weights of fire retardant coatings in Preparation Examples 4-6 (kg) Preparation Example 4 Preparation Example 5 Preparation Example 6 Hollow glass beads 25 20 30 Ammonium Polyphosphate 15 12.5 10 Nano Alumina 8 5 10 Rhododendron 12.5 15 10 Tetraethyl orthosilicate 8 5 10 Epoxy resin 30 15 22 water 30 40 35 Molecular sieve 5 8 3 Example
[0037] Example 1 A fireproof board, the preparation of which comprises the following steps: 80 kg of wood powder is sprayed with ethanol to be evenly moistened, 15 kg of calcium silicate is added and mixed and stirred evenly, and then 12 kg of phenolic resin solution is evenly sprayed and added, and mixed by high-speed stirring to obtain a mixture, which is placed in an oven at 50° C. for 2 hours to be dried, and then the ethanol is removed and placed in a mold, and a layer of glass fiber mesh is laid on the upper and lower surfaces of the substrate respectively, and extrusion molding is performed at 180° C. and 3 MPa to make the glass fiber mesh and the substrate closely combined to form a preliminary board substrate; the phenolic resin solution is an ethanol solution containing 44% phenolic resin; Then, an inorganic fire retardant coating is coated on the surface of the substrate with a coating thickness of 2.2 mm, and cured to obtain a fireproof board; the inorganic fire retardant coating is prepared in Preparation Example 4.
[0038] Example 2 A fireproof board, the preparation of which comprises the following steps: 90 kg of wood powder is sprayed with ethanol to be uniformly moistened, 10 kg of calcium silicate is added and mixed and stirred uniformly, and then 15 kg of phenolic resin solution is evenly sprayed and added, and mixed by high-speed stirring to obtain a mixture, which is placed in an oven at 50° C. for 2 hours to be dried, and then the ethanol is removed, and the mixture is placed in a mold, and a layer of glass fiber mesh is laid on the upper and lower surfaces of the substrate respectively, and extrusion molding is performed at 180° C. and 3 MPa to make the glass fiber mesh and the substrate closely combined to form a preliminary board substrate; the phenolic resin solution is an ethanol solution containing 44% phenolic resin; Then, an inorganic fire retardant coating is coated on the surface of the substrate with a coating thickness of 2.2 mm, and cured to obtain a fireproof board; the inorganic fire retardant coating is prepared in Preparation Example 5.
[0039] Example 3 A fireproof board, the preparation of which comprises the following steps: 100 kg of wood powder is sprayed with ethanol to be evenly moistened, 20 kg of calcium silicate is added and mixed and stirred evenly, then 8 kg of phenolic resin solution is evenly sprayed and added, and mixed by high-speed stirring to obtain a mixture, which is placed in an oven at 50° C. to be dried for 2 hours, after which the ethanol is removed, and placed in a mold, and a layer of glass fiber mesh is laid on the upper and lower surfaces of the substrate respectively, and extruded at 180° C. and 3 MPa to closely combine the glass fiber mesh with the substrate to form a preliminary board substrate; the phenolic resin solution is an ethanol solution containing 44% phenolic resin; Then, an inorganic fire retardant coating is coated on the surface of the substrate with a coating thickness of 2.2 mm, and cured to obtain a fireproof board; the inorganic fire retardant coating is prepared in Preparation Example 6.
[0040] Example 4 A fireproof board, which is different from Example 1 in that the inorganic fireproof coating used in this example is prepared in Preparation Example 7.
[0041] Example 5 A fireproof board material, which is different from Example 1 in that the inorganic fireproof coating used in this example is prepared in Preparation Example 8.
[0042] Example 6 A fireproof board, which is different from Example 1 in that the inorganic fireproof coating used in this example is prepared in Preparation Example 9.
[0043] Example 7 A fireproof board material, which is different from Example 1 in that the inorganic fireproof coating used in this example is prepared in Preparation Example 10.
[0044] Example 8 A fireproof board, which is different from Example 1 in that the glass fiber mesh used in this embodiment is pretreated, specifically comprising the following steps: The glass fiber mesh cloth is immersed in a dipping solution mixed with 3-[tri(1-methylethoxy)silyl]propyl methacrylate and a polyester solution for 2-3 hours, irradiated with ultraviolet light for 3-5 minutes, and dried to obtain the pretreated fiber cloth; the weight ratio of the silicone acrylate to the polyester solution in the dipping solution is 2:1.
[0045] Example 9 A fireproof board material, which is different from Example 8 in that the weight ratio of silicone acrylate to polyester solution added in the dipping solution of this example is 4:1.5.
[0046] Example 10 A fireproof board material, which is different from Example 9 in that the weight ratio of silicone acrylate to polyester solution added in the dipping solution of this example is 3:1.2.
[0047] Comparative Example Comparative Example 1 A fireproof board, which is different from Example 1 in that no glass fiber mesh is added in this example.
[0048] Comparative Example 2 A fireproof board, which is different from Example 1 in that the fireproof coating in this embodiment is directly mixed with the raw materials in the substrate, and the preparation includes the following steps: 80 kg of wood powder is sprayed with ethanol to evenly wet it, 15 kg of calcium silicate is added and mixed, and then 12 kg of phenolic resin solution is evenly sprayed and added, and an equal amount of inorganic fire retardant coating as in Example 1 is added, and the mixture is mixed at high speed to obtain a mixture, which is placed in an oven and dried at 50°C for 2 hours, after which the ethanol is removed and placed in a mold. A layer of glass fiber mesh is laid on the upper and lower surfaces of the substrate respectively, and extrusion molding is performed at 180°C and 3 MPa so that the glass fiber mesh is tightly combined with the substrate to obtain the fireproof board; the phenolic resin solution is an ethanol solution containing 44% phenolic resin; and the inorganic fire retardant coating is prepared in Preparation Example 4.
[0049] Comparative Example 3 A fireproof board material, which is different from Example 1 in that epoxy resin is not added to the fireproof coating in this example.
[0050] Performance testing Detection method / test method The performance test was conducted on the plates prepared in the embodiment and the comparative example, and the plates were cut to have a length of 125 mm, a width of 13 mm, and a thickness of 13 mm; Thermal conductivity: The thermal conductivity of the sample was tested using a thermal conductivity tester; Fireproof performance: According to GB / T 14402-2007 "Determination of combustion value of combustion performance of building materials and products", the combustion value of the prepared board is tested using an automatic calorimeter. The test sample is prepared according to the sample preparation method in 5.9, and the sample is placed in an oxygen bomb for combustion test. The combustion temperature is 2000℃ until the material is carbonized. Because it is a fireproof material, a certain amount of benzoic acid must be added as a combustion aid at a ratio of 1:1 before testing. The test result must subtract the combustion value caused by benzoic acid. The combustion value and weight loss rate are calculated.
[0051] Impact resistance: The impact strength of the sample is measured according to GB / T 11548-1989.
[0052] Table 2 Test results Thermal conductivity (W / m·k) Combustion value (MJ / Kg) Weight loss rate / % Impact strength (KJ / m2) Example 1 0.058 1.5 5 40 Example 2 0.06 1.6 4.5 42 Example 3 0.059 1.55 4.8 41 Example 4 0.057 1.62 4.2 43 Example 5 0.056 1.65 4 44 Example 6 0.063 1.45 6.2 36 Example 7 0.062 1.52 5.9 37 Example 8 0.055 1.49 3.8 45 Example 9 0.054 1.45 3.5 46 Example 10 0.053 1.48 3.2 47 Comparative Example 1 0.075 3 8 29 Comparative Example 2 0.068 3.2 7 33 Comparative Example 3 0.07 2.8 9 30 The total combustion value of Examples 1-10 is less than 3 MJ / Kg, and the weight loss rate is less than 20%, which meets the Class A standard in GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products".
[0053] Combining Examples 1-3 and Comparative Example 1 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that the addition of glass fiber mesh can strengthen the board structure, effectively resist external force impact, and at the same time improve the stability of the board at high temperature, giving the board good fire resistance.
[0054] Combining Examples 1-3 with Comparative Example 2 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 2, indicating that the fire retardant performance of the board prepared by directly mixing the fire retardant coating with the base material is not as good as that of the board prepared by layering. By constructing a reasonable hierarchical structure, it is helpful to prevent the spread of flames and improve the fire retardant performance of the board.
[0055] Combining Examples 1-3 with Comparative Example 3 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3, indicating that no epoxy resin is added to the fire retardant coating, resulting in weakened bonding with the base material, causing the coating of the board to easily fall off or crack when subjected to external force or temperature changes, affecting the fire retardant performance of the board.
[0056] Combining Examples 1-7 and Table 2, it can be seen that the experimental data of Examples 1-5 are better than those of Examples 6-7. In Example 6, no molecular sieve is added, and its fire retardant performance is lower than that of the example with the addition of molecular sieve, indicating that the presence of the porous molecular sieve can adsorb the free radicals generated during combustion, interrupt the chain reaction, and thus significantly improve the fire retardant performance of the fire retardant coating. Combining Example 1 with Example 7, the experimental data of Example 1 are better than those of Example 7, indicating that adding the modified molecular sieve to the fire retardant coating is beneficial to improving the compatibility of the molecular sieve with the coating matrix, improving the uniformity of the dispersion of the molecular sieve in the coating, and introducing flame-retardant element ions into the modified molecular sieve, which effectively improves the fire retardant effect of the coating.
[0057] Combining Example 1 with Examples 8-10 and Table 2, it can be seen that the experimental data of Examples 8-10 are better than those of Example 1, indicating that the active functional groups can adhere to the glass fiber mesh during the pretreatment of the glass fiber mesh with silicone acrylate and polyester solution, further improving the bonding strength between the coating and the substrate. At the same time, the treated glass fiber mesh can maintain better stability at high temperatures, thereby further improving the fireproof effect of the board.
[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A fireproof board, characterized in that: It includes a substrate, a reinforcing layer coated on both sides of the substrate, and a fire-retardant coating coated on the outer surfaces of both sides of the board, wherein the substrate includes wood powder, a silicate compound and a phenolic resin adhesive, and both sides of the substrate are coated with glass fiber mesh as a reinforcing layer, and the surface is coated with the fire-retardant coating; The fire retardant coating comprises the following raw materials in parts by weight: 20-30 parts of hollow glass microspheres, 10-15 parts of ammonium polyphosphate, 5-10 parts of nano metal oxides, 10-15 parts of magnesite, 5-10 parts of tetraethyl orthosilicate, 15-30 parts of epoxy resin, and 30-40 parts of water.
2. A fireproof board according to claim 1, characterized in that: The fire retardant coating also includes 3-8 parts of modified molecular sieves, into which phosphorus and fluorine elements are introduced.
3. A fireproof board according to claim 2, characterized in that: The modified molecular sieve preparation comprises the following steps: Weigh a molecular sieve and soak it in a mixed solution of hypophosphite and 1-butyl-3-methylimidazolium tetrafluoroborate, stir it at room temperature for 1-2 hours, then grind it into powder and dry it to obtain the product.
4. The fireproof board according to claim 1, characterized in that: The weight ratio of the molecular sieve to the hypophosphite and 1-butyl-3-methylimidazolium tetrafluoroborate is 1:0.3:0.5-1.
5. The fireproof board according to claim 1, characterized in that: The glass fiber mesh is pre-treated, and the pre-treatment includes the following steps: The glass fiber mesh cloth is immersed in a dipping solution mixed with silicone acrylate and polyacrylamide solution for 2-3 hours, irradiated with ultraviolet light for 3-5 minutes, and dried to obtain the pretreated fiber cloth.
6. The fireproof board according to claim 1, characterized in that: The weight ratio of silicone acrylate and polyester added in the dipping solution is 2-4:1-1.
5.
7. A method for preparing a fireproof board according to any one of claims 1 to 7, characterized in that: The steps include: The wood powder and silicate compound are mixed and stirred evenly, and the phenolic resin solution is evenly sprayed and added. After high-speed stirring and mixing, a layer of glass fiber mesh is laid on the upper and lower surfaces of the matrix respectively, and a preliminary board matrix is formed through a hot pressing process; The inorganic fireproof coating is coated on the surface of the preliminary board substrate and cured to obtain the fireproof board.
8. A method for preparing a fireproof board according to claim 7, characterized in that: The base material comprises, by weight, 80-100 parts of wood flour, 10-20 parts of silicate compounds and 8-15 parts of phenolic resin.
Citation Information
Patent Citations
Method for preparing moth-proofing cork floor
CN105370010A
Novel magnesian board
CN105735597A
Fireproof nanometer epoxy floor paint
CN106497327A
Fireproof filling product
CN110528096A
Glass fiber cloth reinforced insulating molded board and preparation method thereof
CN113150331A
Cited By
Carbon fiber reinforced polypropylene flame-retardant wear-resistant furniture board and preparation method thereof
CN120842624A
Composite material for chlorinated polyvinyl chloride-based fireproof wood board and preparation method of composite material
CN121403786A
A composite material for fireproofing wood board based on chlorinated polyvinyl chloride and a method for preparing the same
CN121403786B